Radon exhalation rate and natural radioactivity in the building materials used in metropolitan Jakarta and its surrounding areas, Indonesia - Nugraha, Eka Djatnika; Modibo, Oumar Bobbo; Wahyudi,; Pradana, Radhia; Merdekawati, Rima Agustin; Megagasri, Kartini; Topandi, Abdussalam; Rachman, Agus Nur; Kurniawan, Rusbani; Fajrianshah, Evans Azka; Hidayati, Nurahmah; Winarni, Ilma Dwi; et al. (Frontiers in Public Health, 2025)
IntroductionCreating a safe living environment involves using healthy and sustainable building materials. Humans are exposed to natural radionuclides, such as 226Ra, 232Th, and 40K decay series, found in building materials that pose a radiological hazard. This study is aimed to investigate the radionuclides content of building materials used in Jakarta and its surrounding areas. The computer code RESRAD-BUILD was used to calculate the annual effective dose received by an adult living in a typical room constructed with the studied building materials.MethodsSamples such as sand, cement, bricks, and Autoclaved Aerated Concrete (AAC) were collected. The 222Rn surface exhalation rate was determined using the closed chamber method using RAD7, while the activity concentration of natural radionuclide was measured using a gamma spectrometer.Results and discussionThe 222Rn surface exhalation rate varies from 4 × 10−2 to 1.6 × 100 mBq m−2 s−1 with an average of 4 × 10−1 mBq m−2 s−1. The average 222Rn exhalation rate of the building materials studied was much lower than the global average value of 1.6 × 101 mBq m−2 s−1. The average activity concentration values of 232Th (21 Bq kg−1) and 40K (217 Bq kg−1) in all building materials studied are lower than the global average values of 45 and 412 Bq kg−1. In comparison, the average activity concentration of 226Ra (34 Bq kg−1) is similar to the global average value of 32 Bq kg−1. Furthermore, the assessed radiological hazard from the measured building material has an average activity index of 0.3, while the RESRAD-BUILD estimated total annual effective dose for a typical house constructed using a mixture of the building materials was 0.11 mSv, in which indoor 222Rn alone represents 92% of the total. From the assessment results, the building materials in Jakarta and its surrounding areas do not pose significant concerns regarding radiological hazards. However, the higher contribution of 222Rn suggests the need for a large-scale indoor 222Rn survey in the study area.